Literasi peran manajemen dan strategi eksistensi UMKM di Kota Semarang - Irene Nathalia Setiawan; Rivan Ramdani; Wahyu Puspitasari (Abdimas Siliwangi, 2024)
There are many problems currently plaguing UMKM in Indonesia. These challenges include the quality of human resources, inadequate managerial capabilities, limited investment funds and working capital, lack of expertise in marketing strategies and the ability to utilize technology which is still relatively low. UMKM have a lot of room to grow in today's information-based economy, as long as they make good use of existing information technology infrastructure. Therefore, it is very important for stakeholders to continue to carry out outreach, guidance and support for UMKM. Management excellence in the changing dynamics of the Indonesian economy has direct implications for the tactics used by UMKM to survive in the business world, especially in the area of legal compliance. In order for UMKM to grow and develop in today's competitive market, it is important to address legal issues head-on. Through the use of management knowledge, digital technology, and legal registration assistance, community service is realized. It is hoped that UMKM players can remain competitive by maintaining product quality and being able to play a management role in running the gendar cracker business.